Manajemen Sanggar Seni Shaka Budaya Kabupaten Wonogiri - Alfonza Araneki Valentine Hanadayinta; Eny Kusumastuti (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to describe the management of Sanggar Seni Shaka Budaya in Wonogiri Regency, which includes the aspects of planning, organizing, implementation, and supervision. The research used a qualitative approach with a descriptive method through observation, interviews, and documentation techniques. The subjects of the study consisted of the founder of the studio, administrators, instructors, and members of the art studio. The results showed that Sanggar Seni Shaka Budaya, founded by Siti Fatonah or commonly called Mrs. Ifat in 2016, has implemented management functions systematically. The studio originated from the Simbol Jempol Jentik Community in 2015, which later developed into a center for cultural arts preservation in Pracimantoro District, Wonogiri Regency. In the planning aspect, the studio has short-term and long-term work programs such as routine training, art performances, competitions, and dance competency tests. In the organizing aspect, the studio has an organizational structure and a division of duties for instructors based on the students’ class levels. In the implementation aspect, activities are carried out through classical and creative dance training, art performances, and social media publications to attract and maintain members. The studio is also active in participating in various art events at the provincial level and has more than one hundred members. In the supervision aspect, evaluations are conducted directly on participants’ skill development through training and competency tests.